Integrated Reporting Practice and Disclosure in Bangladesh’s Banking Sectors - Niaz Mohammad (Universitas Pasundan, 2019)
Integrated reporting (IR) is a new form of corporate reporting that has emerged after decades of calls by academics and practitioners for more holistic and integrated corporate reporting on the economic, environmental, and social aspects of business. The present research relied on a critical review of the literature on IR practices and sustainability reporting. Indexed journals were reviewed, and evidence was drawn upon to develop a model examining the possible determinants of IR in annual reports. To this end, reports from 20 different banks from 2012 to 2017 were considered. Analyzing the financial statements of these banks through their annual reports provided insightful disclosures concerning triple bottom lines (social, environmental, and economic); the findings of the study suggested that very few banks have taken initiatives to disclose such information in their annual reports. Using annual report content analysis, the findings showed that in 2017, companies started providing non-financial information regarding the environment, society, and governance along with financial figures. However, it is noteworthy that companies still provide this information in disconnected strands and as part of corporate governance or corporate social responsibility disclosures instead of linking such information to financial information and providing it within integrated reports.